The duration of asystolic ischemia determines the risk of graft failure after circulatory‐dead donor kidney transplantation: A Eurotransplant cohort study. Issue 4 (10th November 2017) - Heylen, L.; Jochmans, I.; Samuel, U.; Tieken, I.; Naesens, M.; Pirenne, J.; Sprangers, B.
Abstract : Circulatory death donor (DCD) kidney transplantations are steadily increasing. Consensus reports recommend limiting donor warm ischemia time (DWIT) in DCD donation, although an independent effect on graft outcome has not been demonstrated. We investigated death‐censored graft survival in 18 065 recipients of deceased‐donor kidney transplants in the Eurotransplant region: 1059 DCD and 17 006 brain‐dead donor (DBD) kidney recipients. DWIT was defined as time from circulatory arrest until cold flush. DCD donation was an independent risk factor for graft failure (adjusted hazard ratio [HR] 1.28, 95% CI 1.10‐1.46), due to an increased risk of primary nonfunction (62/1059 vs 560/17 006; P  < .0001). With DWIT in the model, DCD donation was no longer a risk factor, demonstrating that DWIT explains the inferior graft survival of DCD kidneys. Indeed, DCD transplants with short DWIT have graft survival comparable to that of standard‐criteria DBD transplants ( P  = .59). DWIT also associated with graft failure in DCDs (adjusted HR 1.20 per 10‐minute increase, 95% CI 1.03‐1.42). At 5 years after transplantation, graft failure occurred in 14 of 133 recipients (10.5%) with DWIT <10 minutes, 139 of 555 recipients (25.0%) with DWIT between 10 and 19 minutes, and 117 of 371 recipients (31.5%) with DWIT ≥20 minutes. These findings support the expert opinion–based guidelines to limit DWIT. Abstract : Asystolic donor warm ischemia time determines graft survival after circulatory‐dead donor kidney transplantation.